2018
DOI: 10.3390/toxins10090367
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Indoxyl Sulfate and p-Cresol Sulfate on Chronic Kidney Disease and Mitigating Effects of AST-120

Abstract: Uremic toxins, such as indoxyl sulfate (IS) and p-cresol, or p-cresyl sulfate (PCS), are markedly accumulated in the organs of chronic kidney disease (CKD) patients. These toxins can induce inflammatory reactions and enhance oxidative stress, prompting glomerular sclerosis and interstitial fibrosis, to aggravate the decline of renal function. Consequently, uremic toxins play an important role in the worsening of renal and cardiovascular functions. Furthermore, they destroy the quantity and quality of bone. Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 116 publications
(167 reference statements)
0
115
0
Order By: Relevance
“…Our study demonstrated that adsorbents of uremic toxins administered in the perioperative period could attenuate neointima formation and improve patency of AV fistula. AST-120 was developed in 1982 as an oral carbonaceous adsorbent for the binding of IS and PCS precursors in the gastrointestinal tract [38]. It could effectively decrease serum IS and PCS levels in CKD patients without major side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that adsorbents of uremic toxins administered in the perioperative period could attenuate neointima formation and improve patency of AV fistula. AST-120 was developed in 1982 as an oral carbonaceous adsorbent for the binding of IS and PCS precursors in the gastrointestinal tract [38]. It could effectively decrease serum IS and PCS levels in CKD patients without major side effects.…”
Section: Discussionmentioning
confidence: 99%
“…40 Both indoxyl sulfate and FIGURE 1 Crosstalk between gut microbial metabolites and organs beyond the gut through the gut-systemic axis ↑foam cell formation, ↓reverse cholesterol transport, ↑platelet aggregation potential. Target receptor remains unknown 33,34 Indoxyl sulfate Tryptophan Uremic toxin proposed to aggravate chronic renal disease, CVD, as well as CKD related bone disorders 21,35 Enter proximal renal tubular cell through organic anion transporter and cause oxidative stress by activating ROS system 21,35 p-Cresol sulfate Tyrosine, phenylalanine…”
Section: Microbial Metabolites Are Messengers In the Gut-systemic Amentioning
confidence: 99%
“…Uremic toxin ↑cardiovascular mortality in CKD patients. Elevated in urine of colorectal cancer patients 21,36 Exhibits genotoxicity, cytotoxicity in vitro and induces renal interstitial fibrosis and glomerulosclerosis in mice model 21,36 Indolepropionic acid Tryptophan Negatively correlated with low-grade inflammation and type II diabetes mellitus development. Potential antituberculosis effect [37][38][39] Bind to pregame X receptor in intestinal cells and improve mucosal homeostasis and gut barrier function [37][38][39] Imidazole 18 Phytochemicals from plant foods can also be modified by gut microbiota to produce compounds with higher levels of bioactivity.…”
Section: Microbial Metabolites Are Messengers In the Gut-systemic Amentioning
confidence: 99%
See 2 more Smart Citations